Predictors burden in mental health workers during the COVID-19 pandemic - Mombelli, Janaina Maria Rodrigues [UNESP]; Barbosa, Guilherme Correa [UNESP]; Claro, Heloísa Garcia; Boska, Gabriella de Andrade; Oliveira, Márcia Aparecida Ferreira de (FapUNIFESP (SciELO), 2022)
OBJECTIVES: to analyze burden predictors in mental health workers during the COVID-19 pandemic. METHODS: a quantitative study, collected between October and December 2020 through a sociodemographic questionnaire and Mental Health Service Burden Assessment Scale, in four services in a municipality in the state of São Paulo, Brazil, with 108 workers. Descriptive analysis and multiple linear regression of ordinary least squares were performed, in search of predictors for variation in the scale score. RESULTS: it showed median work burden (2.03). Predictors: psychological or psychiatric follow-up; normal performance of activities during the pandemic; direct action with suspected or confirmed cases of COVID-19; and belonging to the risk group (people over 60 years of age, diabetics, hypertensive, cardiac, respiratory problems) (p<0.05). CONCLUSIONS: working conditions observed during the pandemic, simultaneously with workers' mental health care needs predict burden at work in health.